DIW Berlin Economic Outlook: German economy stuck in limbo while trade conflicts threaten the global economy - Geraldine Dany-Knedlik; Guido Baldi; Nina Maria Brehl; Hella Engerer; Angelina Hackmann; Pia Hüttl; Konstantin Kholodilin; Frederik Kurcz; Laura Pagenhardt; Jan-Christopher Scherer; Teresa Schildmann; Hannah Magdalena Seidl; et al. (DIW Weekly Report, 2024)
The German economy is stuck in a difficult position as it faces both slow growth as well as structural change. The continuing lack of orders in manufacturing, increasing international competition, and sluggish development in industry-related services are now affecting the labor market and leading not only to short-time work but to layoffs too, despite the continuing skilled worker shortage. While GDP increased slightly by 0.1 percent in the third quarter of 2023, this growth was preceded by a stronger than initially recorded decline in economic output of 0.3 percent in the second quarter. Thus, the German economy cannot be said to be on a stable growth path. In contrast, leading indicators suggest that economic output will decline again in the fourth quarter, with overall growth for 2024 likely to be 0.2 percent. This means that the German economy will contract for the second year in a row. German industry in particular is experiencing a serious crisis. Foreign trade may temporarily benefit, as many companies despite a lack of demand are expected to increase their exports to the United States in order to get ahead of the possible tariffs that US President-elect Donald Trump announced. However, impending protectionist measures are already having an impact and unsettling local companies, which are therefore postponing investments further. In addition, the economic framework conditions in Germany are unclear and will remain unpredictable until at least the spring when there is a new federal government. All of these factors in conjunction with increasing concerns about their own jobs are unsettling households in Germany, resulting in private consumption failing to pick up speed despite rising real wages. A gradual easing is not expected until mid-2025, when domestic and foreign economic uncertainties will successively lessen. Nevertheless, the German economy should expand by 0.2 percent in 2025. Thus, DIW Berlin is revising its fall forecast downward by 0.7 percentage points. Economic output is expected to increase by 1.2 percent in 2026, although this is partially due to non-recurring effects such as a relatively high number of work days. In regard to the global economy, the boom in the United States will remain a key driver for now, compensating for the sluggish recovery in many other advanced economies as well as China. While the Chinese economy falters, a gradual upswing is continuing in the euro area due to rising purchasing power and falling inflation. In 2024, the global economy is expected to grow by 3.7 percent, while it should grow by 3.6 percent and 3.7 percent in 2025 and 2026, respectively.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook